Enhancing Lifelong Learning Competencies Among Adult Learners: A Study of Motivation and Learning Strategies - J. Edward (PT Mutiara Bustan Ilmu, 2025)
This study investigates the relationship between motivation, learning strategies, and the development of lifelong learning competencies among adult learners. In the context of global educational trends and digital transformation, lifelong learning has become crucial for individuals to remain competitive and adaptable. Using a correlational quantitative approach, data were collected from adult learners enrolled in professional development and vocational training programs. The findings indicate that both learning motivation and learning strategies are significant predictors of lifelong learning competencies. Regression analysis and Structural Equation Modeling (SEM) confirmed that higher motivation and the use of effective learning strategies positively influence the development of lifelong learning competencies. Additionally, demographic factors such as age and program type showed variations in learner outcomes. The results highlight the importance of fostering intrinsic motivation and equipping learners with self-regulated learning strategies to enhance their lifelong learning capacities. This research contributes to the understanding of adult education and offers practical recommendations for educators and program designers to create more effective adult learning environments.